2003
DOI: 10.1016/s0029-7844(02)03070-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of peer counseling on smoking cessation and reduction

Abstract: Peer counseling reduced the number of cigarettes smoked daily but did not increase cigarette abstinence rates. Infant birth weight increases with both smoking cessation and smoking reduction, suggesting that peer counseling intervention programs may improve newborn health despite their failure to affect smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…In studies of predominantly low-income and minority populations, peer mentors have been shown to help support healthy behaviors including breastfeeding, smoking cessation, increased physical activity and maintenance of weight loss. 178,179,183185,187,188,190–193,203210 These studies highlight the potential of peer mentoring as a culturally sensitive means to improving health behaviors and outcomes in minority populations, 149,170,198,202,211,217 but there is no such peer mentoring intervention developed for patients with SLE. There is some evidence that peer mentoring has also led to improvements in positive affect, sleep, social coping and perception of bodily pain in rheumatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of predominantly low-income and minority populations, peer mentors have been shown to help support healthy behaviors including breastfeeding, smoking cessation, increased physical activity and maintenance of weight loss. 178,179,183185,187,188,190–193,203210 These studies highlight the potential of peer mentoring as a culturally sensitive means to improving health behaviors and outcomes in minority populations, 149,170,198,202,211,217 but there is no such peer mentoring intervention developed for patients with SLE. There is some evidence that peer mentoring has also led to improvements in positive affect, sleep, social coping and perception of bodily pain in rheumatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Six of nine studies included Black or African American pregnant smokers as more than fifty percent of the participants (Cinciripini et al, 2010; El-Mohandes et al, 2012; Gielen et al, 1997; Lillington et al, 1995; Ondersma et al, 2012; Windsor et al, 1993), with one of them specifically targeting this group (El-Mohandes et al, 2012). Two studies included Hispanic pregnant smokers as more than fifty percent of the participants (Dornelas et al, 2006; Malchodi et al, 2003), and the remaining study specifically targeted Alaska Native pregnant smokers (Patten et al, 2010). The following subsections will summarize findings on demographic characteristics of minority pregnant smokers and intervention components and relevant outcomes across nine reviewed studies.…”
Section: Resultsmentioning
confidence: 99%
“…The average age range of participants was 23.3–27.9 years old and entered treatment during the first and second trimesters (Cinciripini et al, 2010; El-Mohandes et al, 2012; Gielen et al, 1997; Lillington et al, 1995; Malchodi et al, 2003; Ondersma et al, 2012; Patten et al, 2010; Windsor et al, 1993). Most of the participants were not pregnant for the first time (79%; Gielen et al, 1997; Lillington et al, 1995; Patten et al, 2010); had education of twelve years or less (76%; Cinciripini et al, 2010; El-Mohandes et al, 2012; Malchodi et al, 2003; Patten et al, 2010); were unemployed (66%; Cinciripini et al, 2010; El-Mohandes et al, 2012; Malchodi et al, 2003); were Medicaid-eligible (68%; Cinciripini et al, 2010; El-Mohandes et al, 2012); were unmarried (83%; Cinciripini et al, 2010; Malchodi et al, 2003; Patten et al, 2010); and reported depression or other mood disorders (80%; Cinciripini et al, 2010; El-Mohandes et al, 2012). The range of the number of cigarettes smoked per day during pregnancy was 7.5–13.3 (Cinciripini et al, 2010; Gielen et al, 1997; Malchodi et al, 2003; Ondersma et al, 2012), and one study reported that the average number of cigarettes smoked at pre-pregnancy was 16.3, having decreased that number during pregnancy to 9.8 (Cinciripini et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Smoking and alcohol cessation programmes that exploit peer influences that modify the social network of the target have been shown to be more successful than those that do not. [32][33][34][35][36][37][38] In sum, social network targeting represents a paradigm shift in how we currently implement interventions in global health settings. Many behaviour-change interventions currently seek to target all members of a population; however, face-to-face counselling for behaviour change takes time and resources.…”
Section: Background Neonatal Mortality In Hondurasmentioning
confidence: 99%